Electrical parameters behaviour evaluation of Copper Indium Gallium Diselenide thin-film photovoltaic modules. Issue 1 (31st December 2022) - Benghanem, Mohamed; Boulhidja, Sofiane; Mellit, Adel
ABSTRACT: This paper aims to study the metastability as well as the degradation of Copper Indium Gallium Diselenide (CIGS) thin-film photovoltaic modules. Potential-induced degradation (PID) test has been carried out on a CIGS thin-film module inside a climatic chamber with a high temperature (85°C), and relative humidity (85%). A negative voltage of −1000 V was applied to the active cell circuit with different configurations. Results showed that the GIGS thin-film module experienced drastically degradation, mostly for front and back contact configurations because of the large area of applying the negative voltage. The I-V curve showed losses in electrical parameters of the degraded module mainly in the maximum power and the fill factor (FF). Different changes in performance have been observed in the first hour of the test confirming that the tested modules exhibited metastability with the light soaking (LS) effect by improvement in open-circuit voltage (Voc) and FF. A recovery process has been performed on degraded modules by applying positive voltage of +1000 V, the losses in electrical parameters have been partially recovered to the initial value, this process confirms the effect of a high voltage on modules in PV system.